HUTANG JANGKA PANJANG DAN PROFITABILITAS DI BANK SYARIAH: STUDI PADA PT BANK MUAMALAT INDONESIA - Dyah Fitri Yani (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2016)
Profitability is the company’s ability to generate profits by utilizing all available resources. The size of theprofits for company affected by the increase of debt or bond. This study aim is to analyze the effect of longtermdebt on profitability in PT Bank Muamalat Indonesia in the periode of 1999-2013. This study was analyzedusing multiple linear regression model. Proxies used in the profitability ratio is return on equity (ROE) anddisclosure of long-term debt is based on long-term debt to equity ratio (LDER) and long-term debt to assetratio (LDAR). The results show that LDER has significant effect on profitability, when LDER increases theprofitability of Bank Muamalat Indonesia is also rise, whereas LDAR has no significant effect on profitabilityof PT Bank Muamalat Indonesia.